Allogeneic Stem Cell Transplantation for Myelofibrosis in 2012 - Mclornan, D; Mead, A; Jackson, G; Harrison, C (2012)
Myelofibrosis (MF) is a heterogeneous disease for which long-term, effective medical therapeutic options are currently limited. The role of allogeneic haematopoietic stem cell transplant (AHSCT) in this population, many of whom are elderly, often provides a challenge with regard to the identification of suitable candidates, timing of transplantation in the disease course and choice of conditioning regimen. This review summarizes key findings from published data concerning AHSCT in MF and attempts to provide a state of the art approach to MF-AHSCT in 2012. In addition, we postulate on how the era of JAK inhibition might impact on transplantation for MF. © 2012 Blackwell Publishing Ltd.